Case Report: Transient myeloproliferative disorder with trisomy 21 in blast cells - Zacny, Aleksandra; Saniewska, Barbara; Orzeł, Maria; Borek-Dzięcioł, Beata; Kociszewska-Najman, Bożena (Frontiers in Pediatrics, 2025)
BackgroundTransient myeloproliferative disorder is a clonal myeloproliferative syndrome that occurs in the presence of mutations in the GATA1 gene and chromosome 21 trisomy. It affects almost exclusively newborns with Down syndrome and usually resolves spontaneously. Neonatal leukemia is a rare childhood disease. Its prognosis is worse. We report a novel case of transient myeloproliferative disorder in a neonate without phenotypic features of Down syndrome, emphasizing the importance of comprehensive genetic diagnostics in atypical presentations.Case presentationWe present a case of a 4-day-old female neonate without phenotypic features of Down syndrome with suspected proliferative hematopoietic disease. A blood smear at birth showed severe anemia, leukocytosis and the presence of blasts. Abdominal ultrasound showed hepatosplenomegaly. In the bone marrow, 70.2% blast cell infiltration was described. An abnormal karyotype of 47XX+21 and GATA1 mutation were detected only in the blood cells. Transient myeloproliferative syndrome with t21 mosaicism was diagnosed. The patient received cytoreductive treatment according to the AML BFM protocol.ConclusionsThis case highlights the importance of genetic testing in neonates with congenital anemia and hyperleukocytosis, particularly when Down syndrome is not phenotypically apparent. Detecting trisomy 21 mosaicism and the GATA1 mutation is critical for diagnosing transient myeloproliferative disorder, planning the best treatment and determining prognosis.